Yes: The Symptoms of OCD and Depression Are Discrete and Not Exclusively Negative Affectivity - Moore, Kathleen A.; Howell, Jacqui (Frontiers in Psychology, 2017)
Although Obsessive-Compulsive Disorder (OCD) and Depression are classified as separate disorders, the high incidence of co-morbidity and the strong correlations between measures of each has led to debate about the nature of their relationship. Some authors have proposed that OCD is in fact a mood disorder while others have suggested that the two disorders are grounded in negative affectivity. A third proposition is that depression is an essential part of OCD but that OCD is a separate disorder from depression. The aim in this study was to investigate these diverse propositions in a non-clinical sample and also to determine whether factors implicated in each, that is anxious and depressive cognitions, hopelessness, and self-criticism, would demonstrate commonality as predictors of the symptoms of OCD and of depression. Two hundred participants (59% female) (M age = 34 years, SD = 16) completed the Padua Inventory, Carroll Rating Scale, Cognitions Checklist, Self-Criticism Scale, Beck Hopelessness Scale, Buss-Durkee Hostility Inventory-Revised and a Negative Affectivity Schedule. Results indicated a strong correlation between OCD and depression, depression, and negative affectivity but a weaker relationship between OCD and negative affectivity. Path analyses revealed that both anxious and depressive cognitions, as well as hostility predicted both disorders but the Beta-weights were stronger on OCD. Self-criticism predicted only depression while hopelessness failed to predict either disorder but was itself predicted by depressive cognitions. Depression was a stronger indicator of negative affect than OCD and while OCD positively predicted depression, depression was a negative indicator of OCD. These results support the hypothesis that OCD and depression are discrete disorders and indicate that while depression is implicated in OCD, the reverse does not hold. While both disorders are related to negative affectivity, this relationship is much stronger for depression thus failing to confirm that both are subsumed by a common factor, in this case, negative affectivity. The proposition that depression is part of OCD but that OCD is not necessarily implicated in depression and is, in fact, a separate disorder, is supported by the current model. Further research is required to support the utility of the model in clinical samples.